Ultra morphological changes of root canal dentin induced by 940 nm diode laser: An in-vitro study - Muliya Vidya Saraswathi; Nidambur Vasudev Ballal; Indhya Padinjaral; Subraya Bhat (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of this in-vitro study was to investigate the ultra-morphological changes of the root canal dentin after irradiation with 940 nm diode laser along with 2.5% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA) irrigation. Materials and Methods: Ten freshly extracted human permanent mandibular premolar teeth were selected. Teeth were decoronated and the working length was established. Cleaning and shaping was performed using protaper rotary system and the canals were enlarged up to F3 size. Canals were irrigated with 2.5% NaOCl between each instrument change and later with a final flush of 5 ml of 17% EDTA for 1 min. All the prepared teeth were then longitudinally grooved and split into two halves. One-half of each tooth (Group A) (n = 10) was analyzed without laser irradiation and other half (Group B) (n = 10) was analyzed after irradiation with 1.5 W continuous wave of 940 nm diode laser. Samples from both groups A and B were then subjected to scanning electron microscope analysis. Photomicrographs were taken at 2 mm, 7 mm, and 12 mm from the apex representing the apical, middle, and coronal regions at 2000Χ. Energy dispersive X-ray spectroscopy (EDX) analysis of the same samples was done under EDX analyzer to assess the calcium (Ca), phosphorus (P) and magnesium content and to determine the Ca P ratio. Results: Examination of the surface of the root canals revealed that, at middle and apical thirds smear layer removal was better with laser irradiated group. However, in the coronal third there was no statistically significant difference between both the groups. There was a mild variation in values when both group A and group B were compared to Ca, P, magnesium content, and the Ca phosphorous ratio but the difference was not statistically significant. Conclusion: 940 nm diode laser irradiation of root dentin along with NaOCl and EDTA irrigation, resulted in better removal of smear layer without significant additional loss of mineral content.